Gerakan Pendidikan Perempuan Islam: Studi Kiprah ‘Aisyiyah Di Kota Palu (1965-2015) - Andrayani, Utari (Manaqib: Jurnal Sejarah Peradaban Islam dan Humaniora, 2025)
This article examines the history and development of the ’Aisyiyah Islamic women’s education movement in Palu Bay from 1965 to 2015. The main questions to be addressed are: 1) How did ’Aisyiyah develop in Palu City from 1965 to 2015?; and 2) How did the ’Aisyiyah movement fare in education in Palu City from 1965 to 2015? This paper uses a historical method consisting of four stages: heuristics, source criticism, interpretation, and historiography. This paper finds three things: 1) The ’Aisyiyah organization entered Palu City in 1958, then in 1966 officially became the regional leader, and five individuals from various backgrounds and regions led the organization between 1965 and 2015. 2) In the field of education, ’Aisyiyah established formal, informal, and non-formal schools.